Functional, work-related rehabilitative programming for cancer survivors experiencing cancer-related fatigue. (April 2021) - Dolgoy, Naomi; Brose, Julie M; Dao, Thao; Suderman, Kirsten; Gross, Douglas P; Ho, Chester; Culos-Reed, S Nicole; McNeely, Margaret L
Introduction: Cancer-related fatigue negatively impacts 50–90% of cancer survivors. In North America, approximately 50% of return-to-work interventions initially fail for survivors, with cancer-related fatigue often cited as a barrier to workability. Occupational therapy-driven cancer-related fatigue work-related programming for survivors is sparse, despite many published reviews calling for interdisciplinary interventions; to address work-related performance, specific functional interventions are likely to be needed. Further exploration and a broader understanding of survivors' cancer-related fatigue management, participation in rehabilitative programmes, and plans for return to work are necessary to target survivor needs better. Method: Drawing on social theory, this exploratory descriptive study utilised content and thematic analysis of interviews from 12 survivors to explore and describe the perspectives of survivors experiencing cancer-related fatigue yet desiring to work. Results: Content analysis reflected distinct differences in fatigue-related terminology. Thematic analysis identified three themes specific to cancer-related fatigue and workability: valuing physical wellness, perceived cognitive impacts of cancer-related fatigue on function and workability, and the lack of transition from physical exercise to functional work-related activities. Conclusion: Survivors identified gaps in care related to managing cognitive symptoms and the need for functional, work-related interventions to manage cancer-related fatigue. With their expertise in function, occupational therapists are well positioned to facilitate work-specific interventions, within cancer-specific exercise programming.